2001
DOI: 10.1034/j.1399-3054.2001.1130109.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aluminium‐induced citrate secretion in aluminium‐tolerant soybean (Glycine max) plants

Abstract: Recently, we showed that secretion of citrate in an aluminium (Al) tolerant cultivar soybean (Glycine max) (cv. Suzunari) is a specific response to Al stress [Yang et al. (2000) Physiol Plant 110: 72–77]. Here we investigated the intrinsic mechanisms behind the secretion of citrate induced by Al. The amount of citrate secreted during the 24‐h Al treatment period increased with increasing concentration of Al (0–70 μM). We analysed citrate secretion basically under 3 conditions: (1) by varying light‐exposure, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 34 publications
(64 reference statements)
8
78
2
Order By: Relevance
“…This differs from the earlier report by Ma et al (1997) who found that the rate of secretion continued to increase above 50 mM. This disparity might result from experimental conditions, since Yang et al (2001) demonstrated that even light intensity can affect the Al-induced secretion of citrate from soybean (Glycine max) roots. Finally, the variation in Al-induced oxalic acid efflux along the root was similar in both cultivars, showing a 10-fold greater efflux from the apical 0-to-5-mm region than from the 5-to-10-mm region (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…This differs from the earlier report by Ma et al (1997) who found that the rate of secretion continued to increase above 50 mM. This disparity might result from experimental conditions, since Yang et al (2001) demonstrated that even light intensity can affect the Al-induced secretion of citrate from soybean (Glycine max) roots. Finally, the variation in Al-induced oxalic acid efflux along the root was similar in both cultivars, showing a 10-fold greater efflux from the apical 0-to-5-mm region than from the 5-to-10-mm region (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to a number of previous studies where organic acid secretion from roots was measured in a simple salt solution containing CaCl 2 only (Li et al, 2000;Yang et al, 2001;Piñ eros et al, 2002), we used a complete nutrient solution for soybean seedlings and Murashige and Skoog medium for Arabidopsis seedlings. To avoid contaminating the plasma membrane isolates with endoplasmic membranes, we examined the activity of various inhibitor-sensitive ATPases in both the microsomal and plasma membrane fractions (Table I).…”
Section: Activity Of Plasma Membrane Hmentioning
confidence: 99%
“…Citrate secretion from intact roots of soybean was measured using HPLC according to the method of Yang et al (2001). Citrate secretion from Arabidopsis roots was determined by the method of Delhaize et al (1993), with some modifications.…”
Section: Analysis Of Citratementioning
confidence: 99%
See 2 more Smart Citations